AN ANALYSIS OF STUDENT'S ANXIETY OF ORAL PRESENTATIONS AND PUBLIC SPEAKING IN HIGH EDUCATION - Farida Repelita Waty Kembaren; Salsabila Utami Lubis; Mela Ramadini (VISION, 2022)
The ability to speak is a very important aspect, especially in oral presentations in the learning process. Previously, there was a lot of research evidence showing that many students had a fear of public speaking. For this reason, researchers conducted research using qualitative research methods to find out what problems caused students to experience fear or anxiety in speaking English and also aim to find out what and how the strategies used by students in reducing anxiety when speaking in public. This research was conducted at one of the universities in Medan, by using 6 students of English education as samples taken randomly. This research was conducted by answering questions from the google form that has been provided, so that the samples could describe their answers about common problems faced when speaking in public. The results of this survey identify the causes of students' fear of public speaking and to identify how they can minimize their fear of public speaking.